1993
DOI: 10.2307/3869629
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Elicitor: Induced Bean Proline-Rich Protein mRNA Down-Regulation Is Due to Destabilization That Is Transcription and Translation Dependent

Abstract: In bean cells treated with fungal elicitor, the transcripts of PvPRP1, a gene encoding a proline-rich protein, decreased to ~6% of the original level within 4 hr. The apparent mRNA half-life during the period of rapid degradation was ~45 min. The rate of PvPRP1 gene transcription remained constant over this period, as determined by nuclear run-off assays, indicating a decrease in mRNA stability. By using actinomycin D to block transcription, the half-life of PvPRP1 mRNA in unelicited cells was estimated to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…1 C and D). The disparity between the effect of the DST sequence on the steady-state abundance and the half-life of the HPH transcript (12.5-fold vs. 3-fold) is most likely caused by dampening that is commonly observed when general inhibitors of transcription are used to measure mRNA decay rates (10,35,(37)(38)(39). Nonetheless, it is clear that the DST element has reduced the half-life of the HPH mRNA in 1519-31.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 C and D). The disparity between the effect of the DST sequence on the steady-state abundance and the half-life of the HPH transcript (12.5-fold vs. 3-fold) is most likely caused by dampening that is commonly observed when general inhibitors of transcription are used to measure mRNA decay rates (10,35,(37)(38)(39). Nonetheless, it is clear that the DST element has reduced the half-life of the HPH mRNA in 1519-31.…”
Section: Resultsmentioning
confidence: 99%
“…3A, Table 1), and differences in mRNA abundance are often not fully reflected in differences in mRNA half-lives when measured by using general inhibitors of transcription (10,35,(37)(38)(39), as mentioned earlier. For example, in the case of the HPH mRNA, we observed that the 12.5-fold increase in mRNA abundance of the HPH and HPH-DST mRNA was reflected as a 3-fold increase in measured mRNA stability ( Fig.…”
Section: Increased Stability Of Hph-dst Mrna In Dst1 and Dst2 Comparementioning
confidence: 92%
“…In Arabidopsis it was estimated that 1% of the transcripts have a half-life of < 60 min, and that these highly unstable transcripts are often associated with the circadian timing system and the response to mechanical stimulation (Gutierrez et al, 2002). With respect to pathogen defense, early on destabilization of a transcript encoding the PvPRP1 (Phaseolus vulgaris proline-rich protein (1) cell wall protein in bean has been reported in response to the elicitor of Colletotrichum lindemuthianum (Zhang et al, 1993). The PvPRP1 3′ untranslated region (UTR) interacts with a 50 kDa protein that presumably has a role in mRNA destabilization, as its RNAbinding activity inversely correlates with PvPRP1 mRNA levels (Zhang & Mehdy, 1994).…”
Section: Regulated Rna Stabilitymentioning
confidence: 99%
“…Current models favor parameters inherent to the mRNA itself such as cap structures or poly(A)-tail structures as major regulatory factors for mRNA destabilisation (Sachs, 1993). Destabilisation of mRNAs is an active and selective process, which requires newly synthesized compounds and specific binding to particular sites in an mRNA (Fritz et al, 1991;Zhang et al, 1993, Zhang andMehdy, 1994). In the heat-shock responses, selective degradation of existing mRNAs has been shown to assist in the rapid restructuring of the cellular pattern of protein synthesis (Belanger et al, 1986;Brodl and Ho, 1991).…”
Section: Regulation Of Plant Ribonucleases and Correlation Withyprl0 mentioning
confidence: 99%